1986
DOI: 10.1172/jci112463
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of gentamicin uptake and release in the rat. Comparison of inner ear tissues and fluids with other organs.

Abstract: The kinetics of entry and release of gentamicin was investigated in fluids and tissues of the inner ear of the rat, as well as in renal cortex, and in organs that do not share susceptibility to the toxic effects of aminoglycosides. Various modes of administration were used to achieve different patterns of drug plasma concentrations. Electrophysiological and histological examinations were performed to correlate pharmacokinetics and ototoxicity. Results show that: the uptake of the drug by the inner ear tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(128 citation statements)
references
References 42 publications
8
118
0
2
Order By: Relevance
“…Subsequent studies confirmed the rapid uptake of aminoglycosides into the organ of Corti and endocochlear fluids within 2 h following a single injection (Tran Ba Huy et al, 1986;Tran Ba Huy et al, 1983). More recent studies have used fluorescent probes, immunohistochemistry, autoradiography and electron microscopy to localize aminoglycosides in hair cells up to six months after administration (de Groot et al, 1990;Dulon et al, 1993;Hashino et al, 1997;Imamura and Adams, 2003a;Richardson et al, 1997).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Subsequent studies confirmed the rapid uptake of aminoglycosides into the organ of Corti and endocochlear fluids within 2 h following a single injection (Tran Ba Huy et al, 1986;Tran Ba Huy et al, 1983). More recent studies have used fluorescent probes, immunohistochemistry, autoradiography and electron microscopy to localize aminoglycosides in hair cells up to six months after administration (de Groot et al, 1990;Dulon et al, 1993;Hashino et al, 1997;Imamura and Adams, 2003a;Richardson et al, 1997).…”
Section: Introductionmentioning
confidence: 85%
“…Initial studies of tritiated aminoglycoside uptake showed rapid uptake in endocochlear tissues, cells, and fluids within 2 h (Balogh et al, 1970;Tran Ba Huy et al, 1986;Tran Ba Huy et al, 1983;von Ilberg et al, 1971). Tritiated aminoglycosides cannot distinguish between cytoplasmic and organelle uptake, except by electron microscopy (Hashino et al, 1997;Wedeen et al, 1983), precluding the analysis of subcellular distribution of aminoglycoside uptake in large numbers of individual cell types.…”
Section: Guinea Pigsmentioning
confidence: 99%
“…Pharmacokinetic studies have confirmed this principle (9,34,44,45,46,47). Potential side effects of systemic treatment and complications from a long lasting, higher dose therapy can be avoided through topical application therapy.…”
Section: Introductionmentioning
confidence: 89%
“…Studies in rats have shown that aminoglycosides can be found in the inner ear only minutes after systemic administration and levels plateau within 30 min to 3 h (Tran Ba Huy et al 1986). Clearance of aminoglycosides from both inner ear fluids and tissues is very slow: While the half-life of aminoglycosides in serum is about 3-5 h, they can remain in the inner ear for longer than 30 days (Tran Ba Huy et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Clearance of aminoglycosides from both inner ear fluids and tissues is very slow: While the half-life of aminoglycosides in serum is about 3-5 h, they can remain in the inner ear for longer than 30 days (Tran Ba Huy et al 1986). When exposed to aminoglycosides, hair cells demonstrate both morphologic and molecular features of apoptotic cell death, including condensed, marginated chromatin, and positive terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling staining (Forge and Fradis 1985;Li et al 1995;Lang and Liu 1997;Nakagawa et al 1998;Forge and Li 2000;Matsui et al 2002;Mangiardi et al 2004).…”
Section: Introductionmentioning
confidence: 99%